Beyond condoms: unpacking the complex web of stigma, cost and gender disparities in STI healthcare-seeking among high-risk subgroups in Sub-Saharan Africa - Joseph Opeolu Ashaolu; Steven Ogunbola; Kehinde R. Odewumi; Oluwayemisi Bukola Tanimowo; Sylvain Y. M. Some (Critical Public Health, 2025)
Sexually transmitted infections (STIs) remain one of the leading public health challenges in Nigeria, where structural factors such as stigma and gender differences drive STI disparities. The study objective is to evaluate structural factors and identify high-risk subgroups of STIs through cluster analysis, present the impact of evidence-based interventions via counterfactual modeling, and assess cost-effectiveness through equity-sensitive metrics. Equitable intervention strategies using machine learning (XGBoost, Random Forest, Logistic Regression) on a retrospective database (N=400), from Ekiti State Teaching Hospital, Nigeria (January–October 2024) was modelled. Predictive modeling was used to simulate three scalable interventions which includes peer education/mobile testing for young men, workplace condom programs, and health-care provider trust-building training. Cluster analysis was used to describe STI risk factors and high-risk sub-groups, while cost-effectiveness was evaluated based on incremental cost-effectiveness ratios (ICERs) and quality-adjusted life years (QALYs). Stratification by demographics showed inequalities with young men reporting highest condom use (62.3%), highest stigma (65.1%), but lowest screening rates (41.5%). Our models predicted that mobile testing could increase screening by 32% among stigmatized young men (18–28 years, $78/behavior change), and double stigma reduction in healthcare-seeking (OR=3.45) with $20/participant, and also revealed that workplace programs reproduces gender gaps through under-reaching women in informal sector by 22% ($112/behavior change). Predictive modeling showed condom non-use (OR=4.32), young age (OR=3.45), and low health-care provider trust (OR=2.89) as the strongest predictors of risk. Random Forest produced the highest accuracy (87%), while maximum cost-effectiveness of mobile testing ($222/STI prevented) and workplace programs ($417/STI prevented) were attained. These results highlight the need for multicomponent interventions for (1) holistic STI education beyond sexual transmission, (2) stigma reduction interventions, and (3) increased service accessibility and affordability. These implications are essential to informing Nigeria and other similar low-resource settings’ STI policy and program planning.